Organic soil fertility management practices for the management of fall armyworm, Spodoptera frugiperda (J.E. Smith), in maize - Bayissa, Wakuma; Abera, Asnake; Temesgen, Jibril; Abera, Gemechu; Mendesil, Esayas (Frontiers in Insect Science, 2023)
The fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), is a polyphagous pest native to the Americas. It attacks several crops but in particular causes significant damage to maize, which is a staple crop in Africa. Organic soil amendments have an impact on the physical, chemical, and biological properties of soil, which enhance plant resistance to or tolerance of insect pests and also promote a diverse population of natural enemies of the pest. However, the practices followed for the management of crop residue and animal manure affect their use as organic soil amendments. A field experiment was conducted to evaluate the effect of maize residue and cattle manure incorporation into soil on FAW in the Mana and Omo Nada districts of the Jimma zone, southwest Ethiopia, during the 2018/19 cropping season. Treatment involved three factors: five different levels of maize residue retention (0%, 25%, 50%, 75%, and 100%), different cattle manure storage systems (control, open, steel roof, and grass roof), and two different districts (Mana and Omo Nada). These variables were organized in a randomized complete block design and replicated three times. The infestation and damage ratings were collected from 30 days after planting at 20-day intervals. The results indicated that maize plots with retained crop residue had a significant reduction in FAW infestation compared with plots without maize residue (control) in both study districts. Furthermore, manure-fertilized plants had a lower percentage of FAW infestation when compared with maize plots without cattle manure in both study districts. The lowest severity of FAW infestation was recorded in a plot with 100% of residue incorporated and treated with cattle manure stored under a grass roof in the Mana district. Therefore, conventional tillage with 100% maize residue incorporation and the application of cattle manure stored under a grass roof showed the best result for reducing FAW infestation in maize. However, further studies are important to determine the effect of treatments over seasons and locations on FAW infestation and maize yields.